P11 Impact of opiate substitution therapy on hepatitis C treatment oucomes for persons who inject drugs at injecting equipment provision sites in the advance HCV trial. (28th September 2020) - Byrne, C; Beer, LJ; Dillon, JF
Abstract : Background: ADVANCE HCV participants are prescribed direct acting anti-viral (DAA) treatment (elbasvir/grazoprevir, ± sofosbuvir for 8/12 weeks) for Hepatitis C (HCV). Eligibility requires participants to be active (within prior 3 months) Persons Who Inject Drugs (PWID). The Injecting Equipment Provision Sites (IEPS) in the trial do not provide opiate substitution therapy (OST) and there is no eligibility requirement to be on OST. This abstract reviews the potential impact of: receiving OST at baseline, commencing OST during treatment; and no OST, upon treatment outcomes. Methods: Participants are asked if they are prescribed OST upon study enrolment. At subsequent on-treatment study visits, they are asked if they have been prescribed or stopped OST since enrolment. Participants are tested for Sustained Viral Response at 12 weeks post-treatment (SVR12). If participants do not return for an SVR12 test, they were considered Lost to Follow-up (LTFU). OST, SVR12 and LTFU data were reviewed for all randomised participants, as follow-up is now complete. Results: Data are available for all 129 randomised participants. Forty-nine were on OST prior to treatment. 43 (88%) achieved SVR 12 and 5 (10%) did not and 1 (2%) is deceased due to illicit drug overdose. Ten were prescribed OST after commencing treatment. 9 (90%) achieved SVR 12, 1 (10%) is LTFU. No participants in these two groups stopped their OST prescription at any point prior to finishing treatment. Seventy participants reported no OST prescription. 47 (67%) achieved SVR 12 and 10 did not, 6 (9%) are LTFU and 1 deceased (illicit drug overdose). 6 (9%) did not initiate treatment following diagnosis. Conclusions: Receipt of OST appears to have a positive effect on commencing DAA treatment for HCV, with all participants that did not commence treatment belonging to the cohort who received no OST prescription at any point during or prior to treatment. Obtaining SVR12 also appears to be more likely for those receiving OST either during or prior to treatment in this cohort of PWID, and less likely for those who received no OST prescription at any point (figure 1 ). OST receipt prior to DAA treatment may decrease likelihood to become LTFU, with a higher proportion of LTFU observed in those with no OST prescription prior to treatment, and those who commenced OST during treatment. Disclosures: LJB and CB have no conflicts to disclose. JFD has honoraria for lectures and research grants from Janssen-Cilag, Roche, Merck Sharp & Dohme, AbbVie, Bristol-Myers Squibb, & Gilead. The ADVANCE HCV Trial is funded by Merck, Sharp & Dohme. Elbasvir/Grazoprevir provided by Merck, Sharp & Dohme. Clinicaltrials.gov Number: NCT03236506 . CTA Number: 41692/0019/001-0001.